2002
DOI: 10.3748/wjg.v8.i3.431
|View full text |Cite
|
Sign up to set email alerts
|

Changes of NF-κB, p53, Bcl-2 and caspase in apoptosis induced by JTE-522 in human gastric adenocarcinoma cell line AGS cells: role of reactive oxygen species

Abstract: These findings suggest that reactive oxygen species, NF-kB, p53, bcl-2 and caspase-3 may play an important role in the induction of apoptosis in AGS cells after treatment with JTE-522.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
16
0
1

Year Published

2003
2003
2012
2012

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 48 publications
(19 citation statements)
references
References 34 publications
2
16
0
1
Order By: Relevance
“…Interestingly, the mutated gene product appears to play an active role in tumor progression [39]. ROS has strongly been correlated with p53 mediated apoptosis [40]. Cox-2 has been reported to regulate the expression of p53 and in turn is regulated by NF-kB that is well known for modulation of inflammatory molecules [41].…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, the mutated gene product appears to play an active role in tumor progression [39]. ROS has strongly been correlated with p53 mediated apoptosis [40]. Cox-2 has been reported to regulate the expression of p53 and in turn is regulated by NF-kB that is well known for modulation of inflammatory molecules [41].…”
Section: Discussionmentioning
confidence: 99%
“…These fi ndings indicate that VLPs from AGSV-infected Vero cells make a specifi c reaction and possess the same antigens as those AGSV from the AGS cell line. Bar d 100 nm line reveals multinuclear giant cell formation, 21 inclusion body-like legion,4,7,29 and an IFN response defi ciency,13,14 and carries genes and proteins of SV5 26. In this study, we confi rmed the formation of multinuclear giant cells in the AGS cell line and detected extracellular VLPs on the surface of AGS cells.…”
supporting
confidence: 60%
“…It has been found that cells of different cancers and even different types of cells of a cancer exhibit significantly different sensitivity to TRAIL [14][15][16][17] . Nuclear transcript factor (NF-κB), survivin and Bcl-2 are apoptosis inhibitors and play a key role in the mechanism of anti-apoptosis of tumors [18][19][20][21][22][23][24][25][26][27][28][29] . If the activity of these factors is suppressed, tumor cells can undergo apoptosis and stop growing [30,31] .…”
Section: Introductionmentioning
confidence: 99%